Digital security concerns and threats facing women entrepreneurs - Alexandra Michota (Journal of Innovation and Entrepreneurship, 2013)
Women represent the main economic force in most developing countries. As economies become more and more information-driven, the issues of women's access to and the use of information and communication technologies (ICTs) are growing in importance for both developed and developing economies. Some claim that women are rather technophobic and that men are much better users of digital tools while others argue that women enthusiastically embrace digital communication. The ease with which information and communication technologies can transmit and disseminate information for development is well recognized. However, women's access to ICTs cannot be assumed to occur 'naturally' when gender-blind approaches and technologies are implemented. As a result of profound, gendered applications and implications of ICTs in employment, education, training, and other areas of life, women need encouragement and support to take their rightful place in the information revolution. Research has demonstrated that security and privacy in use of ICT, especially in the internet, are the most important thematic areas of gender concerns which include freedom of expression, privacy of communication, and secure online spaces where vulnerable groups such as women feel unsafe from harassment. The main concern that discourages women to enter dynamically into e-business market is the disclosure of their personal information compared with men who appear willing to be sacrificing their privacy at the altar of profit of electronic commerce. The aims of this research are the following: firstly, to present digital threats and risks facing women entrepreneurs daily while interacting with online communities, secondly, to study security gaps that the privacy policies of popular pages contain, and lastly, to give proof that women justifiably worry about their security and privacy when using online communities and virtual worlds, like the social networking sites. It is certain that these pages are insufficient regarding the privacy of their users due to the lack of adequate security measures letting personal data be exposed and available to others.
Keywords: 650; ICT; women entrepreneurship; e-Business; digital threats; security; privacy